Thraulodes Ulmer 1920 (Ephemeroptera: Leptophlebiidae) from Espírito Santo state, Brazil - Da Silva Raymundo, Thayna; Almeida, Taís Barbosa; Nascimento, Jeane M. C. Do; Salles, Frederico Falcão (Zootaxa, 2021)
Based on material collected during the past 10 years in the State of Espírito Santo and adjacent areas in Minas Gerais, Southeastern Brazil, we identified three species of the genus Thraulodes: T. itatiajanus Traver & Edmunds, for which we present new records and description of the female imago; T. luisae Souto, Da-Silva & Nessimian, first recorded for the state and for which we describe the nymphal stage; and T. alegre sp. nov., described based on male and female imago. The main diagnostic characteristics of the new species are: color of abdominal terga I–VI whitish translucent, terga II–VI with subrectangular dark brown mark near posterior margin and with midway spot; styliger plate triangular and whitish; penes light yellow, with lateral pouch and penes spines long and tapered, with robust bases.